Civil unrest in North Africa: Risks for natural gas supply? - Stefan Lochner; Caroline Dieckhöner (Institute of Energy Economics at the University of Cologne (EWI), 2011)
The uprising and military confrontation in Libya that began in February 2011 has led to disruptions of gas supplies to Europe. An analysis of how Europe has compensated for these missing gas volumes shows that this situation has not affected security of supply. However, this situation would change if the North African uprising were to spread to Algeria. Since Algeria is a much more important gas supplier to Europe than is Libya, more severe consequences would be likely. Applying a natural gas infrastructure model, we investigate the impact of supplier disruptions from both countries for a summer and winter period. Our analysis shows that disruptions in the low-demand summer months could be compensated for, mainly by LNG imports. An investigation of a similar situation at the beginning of the winter shows that security of supply would be severely compromised and that disruptions to Italian consumers would be unavoidable.
Keywords: L95; C61; Q41; Q34; 330; Natural gas; security of supply; network modelling; North Africa; Erdgas; Energieversorgung; EU-Staaten; Politische Unruhen; Libyen; Algerien